Stability of Viable Counts of Lactic Acid Bacteria during Storage of Goat Milk Soft Cheese - WINIATI PUDJI RAHAYU; FERI KUSNANDAR; WIDYA EKA PRAYITNO (Indonesian Society for microbiology, 2011)
The use of goat milk is limited in Indonesia due to lack of good milking practices resulted in disliked goaty smell. One of the method to eliminate this off flavor is by processing the goat milk into soft cheese. The aim of this research was to study the stability of viable starter lactic acid bacteria cultures (Lactobacillus acidophilus FNCC-0051 and L. casei FNCC-0090) during storage of goat milk soft cheese. Three batches of goat milk soft cheeses were produced with different starter cultures L. acidophilus FNCC-0051 (5.0 x 106 cfu mL-1); L. casei FNCC-0090 (5.0 x 106 cfu mL-1); and the mixture of L. acidophilus FNCC-0051 (2.5 x 106 cfu mL-1) and L. casei FNCC-0090 (2.5 x 106 cfu mL-1). The goat milk cheeses had white color and soft. The viable lactic acid bacteria in the goat milk soft cheese reached 109 cfu g-1, which was stable for 8 weeks at 5 °C. Panelists liked goat milk soft cheeses, especially in term of its aroma. The specific aroma produced could mask the disliked goaty smell.